Results of the EURADOS 2017 intercomparison for whole body neutron dosemeters (IC2017n). (July 2020) - Mayer, Sabine; Chevallier, Marie-Anne; Fantuzzi, Elena; Hajek, Michael; Luszik-Bhadra, Marlies; Tanner, Rick; Thomas, David; Vanhavere, Filip
Abstract: The European Radiation Dosimetry Group (EURADOS) has set up intercomparison exercises for personal dosemeters on a regular basis. In 2017, the second EURADOS intercomparison for neutron dosemeters (IC2017n) took place. The intercomparison concerned the performance of neutron dosemeters provided by individual monitoring services to measure neutron personal dose equivalent, H p (10). The irradiations, which included exposures to neutrons and mixed fields of neutrons and photons as commonly encountered in workplaces, were performed in accredited irradiation facilities in terms of H p (10). The range of energies used in the intercomparison extended from thermal to several MeV, with different dose values and angles used. The paper reports on the results of this intercomparison for whole body neutron dosemeters. Highlights: IC2017n was the second EURADOS organized intercomparison exercise for neutron personal dosemeters after IC2012n. It is an important action in neutron dosimetry. International neutron dosimetry intercomparisons have been performed before only every 8–10 years.